High-content wall-broken ganoderma lucidum spore powder tablet and preparation method thereof
By preparing high-content broken wall Ganoderma lucidum spore powder tablets, combined with the combined granulation technology of sorbitol, hydroxypropyl methyl cellulose and sodium carboxymethyl starch, and the combination of silica and magnesium stearate, the problems of low content, low hardness and slow disintegration in existing Ganoderma lucidum spore powder tablets are solved, and the effects of high hardness, low brittleness and rapid disintegration are achieved. They are suitable for coating treatment and improve the edibleness and stability of the product.
Patent Information
- Application Number
- CN202510147883.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-11
- Publication Date
- 2025-04-15
AI Technical Summary
The existing Ganoderma lucidum spore powder tablets have low content, low density, difficult to press, low hardness of tablets, poor taste, and a high dosage is required to achieve the expected effect.
The preparation method of high-content broken wall Ganoderma lucidum spore powder tablets is adopted, including the use of raw materials with 50 to 60 parts of broken wall Ganoderma lucidum spore powder, 30 to 40 parts of sorbitol, 3 to 5 parts of hydroxypropyl methyl cellulose, 5 to 6 parts of sodium carboxymethyl starch, 2.5 to 3.5 parts of silica and 0.8 to 1.2 parts of magnesium stearate. Through wet granulation technology and tableting process, high-content broken wall Ganoderma lucidum spore powder tablets with high hardness, low fragility and easy disintegration were prepared, and coated to solve the dyeing problem.
The preparation of high-content broken wall Ganoderma lucidum spore powder tablets has been achieved, which has the characteristics of high hardness, low fragility and rapid disintegration. It is suitable for further coating, and solves the problems of low content, low hardness and slow disintegration in Ganoderma lucidum spore powder tablets in the prior art, and improves the edibleness and stability of the product.
Smart Images

Figure CN119817793A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of health food, and in particular relates to a high-content broken-wall ganoderma spore powder tablet and a preparation method thereof. Background Art
[0002] Lingzhi (Latin name: Ganoderma lucidum (Curtis) P. Karst.) is a fungus of the Ganoderma family and the genus Ganoderma. It is a traditional Chinese precious medicinal material for strengthening the body and nourishing the body. Lingzhi spores are extremely tiny oval reproductive cells ejected from the gills of Lingzhi during the growth and maturity period, that is, the seeds of Lingzhi. They have a double-walled structure and are surrounded by hard chitin cellulose. They are difficult for the human body to fully absorb. After the wall is broken, it is more suitable for direct absorption by the human stomach and intestines. The broken wall Lingzhi spore powder contains a large amount of bioactive substances such as polysaccharides and terpenes, which have multiple functions such as regulating immunity, protecting the liver, anti-inflammatory, lowering blood lipids, and anti-radiation. It has become a very important raw material in the big health industry.
[0003] At present, the products related to Ganoderma lucidum spore powder on the market mainly exist in the form of powder, granule, capsule and other dosage forms. Among these dosage forms, the powder has poor fluidity, high oil content, is easily oxidized, and is easy to stick to the surface of the container or packaging; both powder and granule are easy to absorb moisture and change, affecting the product quality, and have a poor taste, which seriously affects its edibility; the contents of the capsule are powdery or granular, with low density, so the capsule filling volume is small, and the characteristics of poor fluidity and high oil content of Ganoderma lucidum spore powder make it account for a small proportion of the contents, so the dosage of the capsule is large. Making the broken wall Ganoderma lucidum spore powder into tablets can well solve the above problems, and the tablets are easy to carry and eat.
[0004] Since the broken wall Ganoderma lucidum spore powder is rich in oil, has low density and high toughness, tablets with broken wall Ganoderma lucidum spore powder accounting for more than 50% in the formula are difficult to be pressed into tablets, the tablets are loose, and the hardness and friability are unqualified; in addition, the broken wall Ganoderma lucidum spore powder is darker in color, dark brown or brown, and its rich polysaccharides, triterpenoid compounds and other ingredients have certain adsorption and chemical reactivity, and are easy to react with oral mucosa and teeth and other surfaces. Therefore, the broken wall Ganoderma lucidum spore powder is easy to stain the oral cavity or other contact objects. Although this problem can be solved by coating, the coating requires the plain tablets to have good hardness and friability, which means that the content of broken wall Ganoderma lucidum spore powder in the broken wall Ganoderma lucidum spore powder coated tablets cannot be too high. If the hardness and friability are improved by adjusting the parameters of the tableting equipment, the tableting process is easy to stick, the tablets are not easy to disintegrate, and the effective ingredients are released slowly. The low proportion of broken wall Ganoderma lucidum spore powder means that a higher dosage is required to achieve the expected effect. In the related research on Ganoderma lucidum spore powder tablets that have been made public so far, the proportion of Ganoderma lucidum spore powder is mostly less than 40%. The Ganoderma lucidum spore powder tablets with a higher proportion have a lower tablet hardness, which is not conducive to the market circulation of the product, nor suitable for further coating, and cannot avoid the product dyeing problem. It also disintegrates slowly, affecting the absorption and onset speed. Summary of the invention
[0005] In view of the above technical problems, the present invention provides a high-content broken-wall Ganoderma lucidum spore powder tablet and a preparation method thereof. The high-content broken-wall Ganoderma lucidum spore powder tablet provided by the present invention has a high proportion of broken-wall Ganoderma lucidum spore powder, uniform color, high hardness, low friability, and easy disintegration, which solves the problem that the prior art cannot simultaneously meet the requirements of high proportion of broken-wall Ganoderma lucidum spore powder, high hardness, low friability, and rapid disintegration.
[0006] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions: The first aspect of the present invention provides a high-content broken-wall Ganoderma lucidum spore powder tablet, comprising the following raw materials in parts by weight: 50-60 parts of broken wall ganoderma spore powder, 30-40 parts of sorbitol, 3-5 parts of hydroxypropyl methylcellulose, 5-6 parts of sodium carboxymethyl starch, 2.5-3.5 parts of silicon dioxide and 0.8-1.2 parts of magnesium stearate.
[0007] The combined use of sorbitol, hydroxypropyl methylcellulose and sodium carboxymethyl starch in the present invention can strengthen the adhesion of the broken wall ganoderma spore powder, so that the broken wall ganoderma spore powder in the tablet has a high proportion, and the hardness of the tablet is improved, the friability is reduced, and it is not easy to break during production and transportation, and can meet the requirements of coating. At the same time, the combination of sorbitol, hydroxypropyl methylcellulose and sodium carboxymethyl starch can also make the tablet easy to disintegrate.
[0008] Silicon dioxide has a certain adsorption effect on the oil released by the broken spore powder of Ganoderma lucidum. On the one hand, it can solve the problem of oil spots that are prone to occur during tableting and improve product stability. On the other hand, the combination of silicon dioxide and magnesium stearate can prevent the above raw materials from sticking during tableting, which is conducive to the smooth progress of tableting.
[0009] Preferably, the high-content broken-wall Ganoderma lucidum spore powder tablets include the following raw materials in parts by weight: 50-60 parts of broken-wall Ganoderma lucidum spore powder, 30-40 parts of sorbitol, 3-5 parts of hydroxypropyl methylcellulose, 5.5 parts of sodium carboxymethyl starch, 3 parts of silicon dioxide, and 1 part of magnesium stearate.
[0010] Preferably, the wall-breaking rate of the broken Ganoderma lucidum spore powder is not less than 98%.
[0011] Preferably, the viscosity of the hydroxypropyl methylcellulose is 50 mPa·s.
[0012] Preferably, the raw materials of the high-content broken-wall Ganoderma lucidum spore powder tablets also include antioxidants.
[0013] The oil rich in broken wall Ganoderma lucidum spore powder is easily oxidized. The presence of antioxidants in the raw materials is helpful to avoid or slow down the oxidation of oil.
[0014] More preferably, the antioxidant is one or both of vitamin C and vitamin E.
[0015] More preferably, the weight portion of the antioxidant does not exceed 0.1 part.
[0016] More preferably, the antioxidant is 0.01-0.02 parts of vitamin C and 0.005-0.0085 parts of vitamin E.
[0017] The second aspect of the present invention provides a method for preparing the high-content broken-wall Ganoderma lucidum spore powder tablet, comprising the following steps: S1. According to the principle of equal and incremental mixing, the broken wall Ganoderma lucidum spore powder, sorbitol, hydroxypropyl methylcellulose and sodium carboxymethyl starch are uniformly mixed to obtain a mixed powder; S2, adding water to the mixed powder to obtain a soft material, granulating to obtain wet granules; drying the wet granules until the moisture content of the granules is 2.5% to 5.0% to obtain dry granules; granulating the dry granules to obtain granulated granules; S3, uniformly mixing the whole granules with silicon dioxide, antioxidants, and magnesium stearate to obtain total mixed granules; S4, tableting the total mixed granules to obtain the high-content broken-wall Ganoderma lucidum spore powder tablets.
[0018] The preparation method utilizes the combination of sorbitol, hydroxypropyl methylcellulose and sodium carboxymethyl starch, adopts a wet granulation technology to change the fluidity and compressibility of the wall-broken ganoderma spore powder, solves the oiling problem in the tableting process by the encapsulation effect of silicon dioxide, and solves the sticking problem in the tableting process by the combination of silicon dioxide and magnesium stearate, and finally obtains high-content wall-broken ganoderma spore powder tablets that meet the requirements of tablets, and the obtained product can meet the requirements of high hardness and low friability, and is suitable for further coating.
[0019] Preferably, the particle size of the broken wall-cracked Ganoderma lucidum spore powder in S1 is less than 550 µm, the particle size of the sorbitol is less than 830 µm; the particle size of the hydroxypropyl methylcellulose is less than 180 µm, and the particle size of the sodium carboxymethyl starch is less than 180 µm.
[0020] Preferably, the mass ratio of the mixed powder to water in S2 is 100:(27-33).
[0021] Preferably, the mesh size of the granulation in S2 is 20-24 meshes.
[0022] Preferably, the drying temperature in S2 is 40-50°C.
[0023] Further preferably, the drying method is: first drying with hot air circulation at 40-50° C. for 16-24 hours, and then air-drying in a cool and dry place for 8-12 hours.
[0024] Preferably, the sieve mesh of the granules in S2 is 24 mesh.
[0025] Preferably, in S3, silicon dioxide is firstly mixed with the whole particles, and then the antioxidant and magnesium stearate are added and mixed evenly.
[0026] Preferably, the tablet weight is adjusted to 0.6-0.8g during tableting as described in S4, and the pressure is adjusted so that the maximum hardness of the tablet is obtained during compression. The maximum hardness that can be achieved by tablets pressed from different materials depends on the properties of the material itself, rather than on the maximum pressure that the tablet pressing equipment can give. If the pressure applied by the tablet pressing equipment is too large, a small amount of material will be squeezed out from the gap between the punch and the die hole, resulting in a decrease in the hardness of the tablet. In the present invention, "adjusting the pressure so that the maximum hardness of the tablet is obtained during compression" refers to adjusting the pressure of the tablet pressing facility for the specific raw material of the broken wall Ganoderma lucidum spore powder tablet, so that the hardness of the tablet obtained by pressing the raw material reaches the maximum value that can be achieved.
[0027] Preferably, the preparation method further comprises coating the high-content cracked ganoderma lucidum spore powder tablets obtained in S4 to solve the problem that the cracked ganoderma lucidum spore powder tablets are prone to staining the oral cavity and other contact objects.
[0028] More preferably, the coating is a gastric soluble film coating. The coating material is preferably a gastric soluble film coating premix that complies with the State Food and Drug Administration standard YBH05682010.
[0029] Further preferably, the coating operation is: dissolving the coating material in 70%~80% ethanol with a solid-liquid ratio of (8~12):(88~92) to obtain a coating solution; coating with the coating solution with a coating weight gain of 3.5%~4.5%.
[0030] The beneficial effects of the present invention are: (1) The present invention adopts the combined granulation of high-content Ganoderma lucidum spore powder with sorbitol, hydroxypropyl methylcellulose and sodium carboxymethyl starch to strengthen the binding effect on the broken wall Ganoderma lucidum spore powder, so that the broken wall Ganoderma lucidum spore powder tablets have the advantages of high content of broken wall Ganoderma lucidum spore powder, uniform color, high hardness, good taste, easy disintegration, and the tablets are suitable for coating, which solves the problems of low content of Ganoderma lucidum spore powder, low density, difficulty in tableting, low tablet hardness, inability to coat, and poor taste in the current health food field. The high-content broken wall Ganoderma lucidum spore powder tablets after coating can further increase the product stability and antioxidant properties.
[0031] (2) The present invention uses silicon dioxide to cover the surface of the particles, making it less likely to stick during the tableting process. At the same time, silicon dioxide also has a certain adsorption effect on the oil released by the broken-wall Ganoderma lucidum spore powder, solving the problem of oil spots that are easy to appear in tablets and further improving the stability of the broken-wall Ganoderma lucidum spore powder tablets.
[0032] (3) All raw materials of the high-content broken-wall Ganoderma lucidum spore powder tablets of the present invention are raw materials that can be used for health food, and their sources are legal. The daily dosage of each raw material meets the relevant requirements, the formula is scientific, and the dosage is reasonable. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 1 is a process flow chart of embodiments 1 to 4 of the present invention. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work fall within the scope of protection of the present invention.
[0035] The broken wall Ganoderma lucidum spore powder is rich in oil, and has a small particle size, low density, and high toughness. When it is made into tablets, its proportion cannot be too high, otherwise it is difficult to press the tablets, the tablets are loose, and the hardness and friability are unqualified. In addition, the broken wall Ganoderma lucidum spore powder is easy to stain the oral cavity or other contact objects. If this problem is solved by coating, the plain tablets need to have good hardness and friability, so the content of broken wall Ganoderma lucidum spore powder in the plain tablets cannot be too high. If the parameters of the tableting equipment are used to promote tablet forming, increase hardness, and improve friability, the resulting tablets are not easy to disintegrate, the effective ingredients are released slowly, and the tableting process is easy to stick.
[0036] In view of the above problems, the embodiment of the present invention provides a high-content broken-wall Ganoderma lucidum spore powder tablet, comprising the following raw materials in parts by weight: 50-60 parts of broken wall Ganoderma lucidum spore powder, 30-40 parts of sorbitol, 3-5 parts of hydroxypropyl methylcellulose, 5-6 parts of sodium carboxymethyl starch, 2.5-3.5 parts of silicon dioxide, and 0.8-1.2 parts of magnesium stearate.
[0037] As a preferred embodiment of the present invention, the raw material further includes an antioxidant.
[0038] The embodiment of the present invention also provides a method for preparing the above-mentioned high-content broken-wall Ganoderma lucidum spore powder tablet, comprising the following steps: S1. According to the principle of equal and increasing mixing, the broken wall Ganoderma lucidum spore powder, sorbitol, hydroxypropyl methylcellulose and sodium carboxymethyl starch are uniformly mixed to obtain a mixed powder; S2, adding water to the mixed powder to obtain a soft material, granulating to obtain wet granules; drying the wet granules until the moisture content of the granules is 2.5% to 5.0% to obtain dry granules; granulating the dry granules to obtain granulated granules; S3, uniformly mixing the whole granules with silicon dioxide, antioxidants, and magnesium stearate to obtain total mixed granules; S4, tableting the total mixed granules to obtain high-content broken-wall Ganoderma lucidum spore powder tablets.
[0039] As a preferred embodiment of the present invention, the preparation method further comprises coating the high-content broken-wall Ganoderma lucidum spore powder tablets obtained in S4.
[0040] The scheme of the present invention is described below through specific embodiments.
[0041] In the following examples and comparative examples, the wall-breaking rate of the broken spore powder of Ganoderma lucidum is 99%, the viscosity of hydroxypropyl methylcellulose is 50 mPa·s, and the coating premix is a gastric-soluble film coating premix purchased from Hebei Zhongcheng Pharmaceutical Technology Co., Ltd. (the main components are hydroxypropyl methylcellulose and polyethylene glycol, which conforms to the standard YBH05682010 of the State Food and Drug Administration).
[0042] Unless otherwise specified, the operating methods or experimental methods used in the following examples are all conventional methods in the art. The raw materials, equipment, etc. used in the following examples are all obtained from commercial sources unless otherwise specified.
[0043] Example 1 This embodiment provides a high-content broken-wall Ganoderma lucidum spore powder tablet, which is made of the following raw materials in parts by weight: 50 parts of broken wall ganoderma lucidum spore powder, 40 parts of sorbitol, 3 parts of hydroxypropyl methylcellulose, 5.5 parts of sodium carboxymethyl starch, 3 parts of silicon dioxide, 1 part of magnesium stearate, 0.013 parts of vitamin C, and 0.0065 parts of vitamin E.
[0044] The preparation method is as follows: Sieving: pass the broken wall Ganoderma lucidum spore powder through a 30-mesh sieve, pass the sorbitol through a 20-mesh sieve, and pass the hydroxypropyl methylcellulose and sodium carboxymethyl starch through an 80-mesh sieve.
[0045] Mixing: According to the principle of equal-incremental mixing, the sieved broken wall Ganoderma lucidum spore powder, sorbitol, hydroxypropyl methylcellulose, and sodium carboxymethyl starch are mixed in a two-dimensional mixer, the frequency of the two-dimensional mixer is set to 50 Hz, and the mixing time is 10 minutes. After mixing, a mixed powder is obtained; Granulation: add 30% water of the material mass to the mixed powder in the two-dimensional mixer, stir for 5 minutes to make a soft material, and then pass it through a swing granulator and a 20-mesh screen to obtain wet granules; Drying: Place the wet granules in a hot air circulation drying oven, set the temperature to 40℃-50℃, dry for 16 hours, and then place in a cool and dry place to dry for 8 hours until the moisture content is 2.5% (the measured moisture content at each sampling point is 2.5%-5.0%, and the average moisture content is 2.5%) to obtain dry granules; Granulation: The dry granules are passed through a 24-mesh sieve through an oscillating granulator again to obtain granules; Total mixing: mixing silicon dioxide and whole granules evenly, then adding antioxidant and magnesium stearate and mixing evenly to obtain total mixed granules; Tableting: The total mixed granules are tableted, and the loading amount is adjusted during tableting so that the tablet weight is 0.6-0.8g, and the pressure of the tablet press is adjusted so that the tablet has the maximum hardness during compression. The high-content broken wall Ganoderma lucidum spore powder tablets are obtained; Coating: Add the coating premix into 75% ethanol to make the solid-liquid ratio of 10:90, and obtain the coating solution after it is fully dissolved; use the coating solution to coat the high-content broken-wall Ganoderma lucidum spore powder tablets in a coating pan to increase the weight of the tablets by 4% (the measured weight increase range is 3.5%~4.5%, and the average weight increase is 4%), and the final product is obtained.
[0046] Process flow chart Figure 1shown.
[0047] Example 2 This embodiment provides a high-content broken-wall Ganoderma lucidum spore powder tablet, which is made of the following raw materials in parts by weight: 60 parts of broken wall ganoderma lucidum spore powder, 30 parts of sorbitol, 5 parts of hydroxypropyl methylcellulose, 5.5 parts of sodium carboxymethyl starch, 3 parts of silicon dioxide, 1 part of magnesium stearate, 0.013 parts of vitamin C, and 0.0065 parts of vitamin E.
[0048] The preparation method is as follows: Sieving: pass the broken wall Ganoderma lucidum spore powder through a 30-mesh sieve, pass the sorbitol through a 20-mesh sieve, and pass the hydroxypropyl methylcellulose and sodium carboxymethyl starch through an 80-mesh sieve.
[0049] Mixing: According to the principle of equal-incremental mixing, the sieved broken wall Ganoderma lucidum spore powder, sorbitol, hydroxypropyl methylcellulose, and sodium carboxymethyl starch are mixed in a two-dimensional mixer, the frequency of the two-dimensional mixer is set to 50 Hz, and the mixing time is 15 minutes. After mixing, a mixed powder is obtained; Granulation: add 33% water of the material mass to the mixed powder in the two-dimensional mixer, stir for 5 minutes to make a soft material, and then pass it through a swing granulator and a 24-mesh screen for granulation to obtain wet granules; Drying: Place the wet granules in a hot air circulation drying oven, set the temperature to 40℃-50℃, dry for 24 hours, and then place in a cool and dry place to dry for 12 hours until the moisture content is 4.0% (the measured moisture content at each sampling point is 2.5%-5.0%, and the average moisture content is 4.0%) to obtain dry granules; Granulation: The dry granules are passed through a 24-mesh sieve through an oscillating granulator again to obtain granules; Total mixing: mixing silicon dioxide and whole granules evenly, then adding antioxidant and magnesium stearate and mixing evenly to obtain total mixed granules; Tableting: The total mixed granules are tableted, and the loading amount is adjusted during tableting so that the tablet weight is 0.6-0.8g, and the pressure of the tablet press is adjusted so that the tablet has the maximum hardness during compression. The high-content broken wall Ganoderma lucidum spore powder tablets are obtained; Coating: Add the coating premix into 75% ethanol to make the solid-liquid ratio of 10:90, and obtain the coating solution after it is fully dissolved; use the coating solution to coat the high-content broken-wall Ganoderma lucidum spore powder tablets in a coating pan to increase the weight of the tablets by 4% (the measured weight increase range is 3.5%~4.5%, and the average weight increase is 4%), and the final product is obtained.
[0050] Process flow chart Figure 1 shown.
[0051] Example 3 This embodiment provides a high-content broken-wall Ganoderma lucidum spore powder tablet, which is made of the following raw materials in parts by weight: 50 parts of broken wall ganoderma spore powder, 40 parts of sorbitol, 3 parts of hydroxypropyl methylcellulose, 5 parts of sodium carboxymethyl starch, 2.5 parts of silicon dioxide, 1.2 parts of magnesium stearate, 0.02 parts of vitamin C, and 0.0085 parts of vitamin E.
[0052] The preparation method is as follows: Sieving: pass the broken wall Ganoderma lucidum spore powder through a 30-mesh sieve, pass the sorbitol through a 20-mesh sieve, and pass the hydroxypropyl methylcellulose and sodium carboxymethyl starch through an 80-mesh sieve.
[0053] Mixing: According to the principle of equal-incremental mixing, the sieved broken wall Ganoderma lucidum spore powder, sorbitol, hydroxypropyl methylcellulose, and sodium carboxymethyl starch are mixed in a two-dimensional mixer, the frequency of the two-dimensional mixer is set to 50 Hz, and the mixing time is 10 minutes. After mixing, a mixed powder is obtained; Granulation: add 27% water of the material mass to the mixed powder in the two-dimensional mixer, stir for 5 minutes to make a soft material, and then pass it through a swing granulator and a 20-mesh screen for granulation to obtain wet granules; Drying: Place the wet granules in a hot air circulation drying oven, set the temperature to 40℃~50℃, dry for 16 hours, and then place in a cool and dry place to dry for 12 hours until the moisture content is 3.2% (the measured moisture content at each sampling point is 2.5%~5.0%, and the average moisture content is 3.2%), and obtain dry granules; Granulation: The dry granules are passed through a 24-mesh sieve through an oscillating granulator again to obtain granules; Total mixing: mixing silicon dioxide and whole granules evenly, then adding antioxidant and magnesium stearate and mixing evenly to obtain total mixed granules; Tableting: The total mixed granules are tableted, and the loading amount is adjusted during tableting so that the tablet weight is 0.6-0.8g, and the pressure of the tablet press is adjusted so that the tablet has the maximum hardness during compression. The high-content broken wall Ganoderma lucidum spore powder tablets are obtained; Coating: Add the coating premix into 80% ethanol to make the solid-liquid ratio of 8:92, and obtain the coating solution after it is fully dissolved; use the coating solution to coat the high-content broken-wall Ganoderma lucidum spore powder tablets in a coating pan to increase the weight of the tablets by 3.9% (the actual measured weight increase range is 3.5%~4.5%, and the average weight increase is 3.9%), and the final product is obtained.
[0054] Process flow chart Figure 1 shown.
[0055] Example 4 This embodiment provides a high-content broken-wall Ganoderma lucidum spore powder tablet, which is made of the following raw materials in parts by weight: 50 parts of broken wall ganoderma spore powder, 40 parts of sorbitol, 3 parts of hydroxypropyl methylcellulose, 6 parts of sodium carboxymethyl starch, 3.5 parts of silicon dioxide, 0.8 parts of magnesium stearate, 0.01 parts of vitamin C, and 0.005 parts of vitamin E.
[0056] The preparation method is as follows: Sieving: pass the broken wall Ganoderma lucidum spore powder through a 30-mesh sieve, pass the sorbitol through a 20-mesh sieve, and pass the hydroxypropyl methylcellulose and sodium carboxymethyl starch through an 80-mesh sieve.
[0057] Mixing: According to the principle of equal-incremental mixing, the sieved broken wall Ganoderma lucidum spore powder, sorbitol, hydroxypropyl methylcellulose, and sodium carboxymethyl starch are mixed in a two-dimensional mixer, the frequency of the two-dimensional mixer is set to 50 Hz, and the mixing time is 15 minutes. After mixing, a mixed powder is obtained; Granulation: add 33% water of the material mass to the mixed powder in the two-dimensional mixer, stir for 5 minutes to make a soft material, and then pass it through a swing granulator and a 24-mesh screen for granulation to obtain wet granules; Drying: Place the wet granules in a hot air circulation drying oven, set the temperature to 40℃~50℃, dry for 24 hours, and then place in a cool and dry place to dry for 8 hours until the moisture content is 4.6% (the measured moisture content at each sampling point is 2.5%~5.0%, and the average moisture content is 4.6%), and obtain dry granules; Granulation: The dry granules are passed through a 24-mesh sieve through an oscillating granulator again to obtain granules; Total mixing: mixing silicon dioxide and whole granules evenly, then adding antioxidant and magnesium stearate and mixing evenly to obtain total mixed granules; Tableting: The total mixed granules are tableted, and the loading amount is adjusted during tableting so that the tablet weight is 0.6-0.8g, and the pressure of the tablet press is adjusted so that the tablet has the maximum hardness during compression. The high-content broken wall Ganoderma lucidum spore powder tablets are obtained; Coating: Add the coating premix into 70% ethanol to make the solid-liquid ratio of 12:88, and obtain the coating solution after it is fully dissolved; use the coating solution to coat the high-content broken-wall Ganoderma lucidum spore powder tablets in a coating pan to increase the weight of the tablets by 4.2% (the actual measured weight gain range is 3.5%~4.5%, and the average weight gain is 4.2%), and the final product is obtained.
[0058] Process flow chart Figure 1 shown.
[0059] Example 5 This embodiment provides a high-content cracked spore powder tablet of Ganoderma lucidum, whose raw materials are basically the same as those in Example 1, except that it does not contain an antioxidant. The raw material composition is as follows: 50 parts of cracked spore powder of Ganoderma lucidum, 40 parts of sorbitol, 3 parts of hydroxypropyl methylcellulose, 5.5 parts of sodium carboxymethyl starch, 3 parts of silicon dioxide, and 1 part of magnesium stearate.
[0060] The preparation method is the same as that of Example 1, the granulation process is smooth, the granules are uniform, and the hardness of the dry granules is moderate.
[0061] Example 6 This embodiment provides a high-content broken-wall Ganoderma lucidum spore powder tablet, the raw materials of which are the same as those in Example 1, and the preparation method is basically the same as that in Example 1, except that no coating is performed.
[0062] Comparative Example 1 This comparative example provides a high-content broken wall Ganoderma lucidum spore powder tablet, the raw materials of which are basically the same as those in Example 1, except that hydroxypropyl methylcellulose is replaced with povidone K30. The raw material composition is as follows: 50 parts of broken wall ganoderma spore powder, 40 parts of sorbitol, 3 parts of povidone K30, 5.5 parts of sodium carboxymethyl starch, 3 parts of silicon dioxide, 1 part of magnesium stearate, 0.013 parts of vitamin C, and 0.0065 parts of vitamin E.
[0063] The preparation method is the same as that of Example 1, but the material is stickier during the granulation process, the granules are more solid, the dry granules are harder, and more plain tablets are scattered, broken, and broken during the coating process, and adhesion is formed between the coated tablets.
[0064] Comparative Example 2 This comparative example provides a high-content cracked spore powder tablet of Ganoderma lucidum, whose raw materials are basically the same as those in Example 1, except that sodium carboxymethyl starch is replaced with corn starch. The raw material composition is as follows: 50 parts of cracked spore powder of Ganoderma lucidum, 40 parts of sorbitol, 3 parts of hydroxypropyl methylcellulose, 5.5 parts of corn starch, 3 parts of silicon dioxide, 1 part of magnesium stearate, 0.013 parts of vitamin C, and 0.0065 parts of vitamin E.
[0065] The preparation method is the same as that of Example 1, the granulation process is smooth, the granules are uniform, and the hardness of the dry granules is moderate.
[0066] Comparative Example 3 This comparative example provides a high-content broken-wall Ganoderma lucidum spore powder tablet, the raw materials of which are the same as those in Example 1, except that the preparation method is different. The specific preparation method is as follows: Sieving: pass the broken wall Ganoderma lucidum spore powder through a 30-mesh sieve, pass the sorbitol through a 20-mesh sieve, and pass the hydroxypropyl methylcellulose and sodium carboxymethyl starch through an 80-mesh sieve.
[0067] Mixing: According to the principle of equal-incremental mixing, the sieved broken wall Ganoderma lucidum spore powder, sorbitol, hydroxypropyl methylcellulose, and sodium carboxymethyl starch are placed in a high-efficiency wet granulator, and the stirring speed is set to 50 Hz and the mixing time is 15 minutes. After mixing, a mixed powder is obtained; Granulation: Turn on the cutter switch of the high-efficiency wet granulator, set the cutter speed to 35HZ, add 30% of the material weight of water to granulate, pump the wet granules into the boiling one-step granulator through the pipeline, set the inlet temperature to 50℃, the outlet temperature to 40℃, dry until the granule moisture content is 2.5%~5.0%, and obtain dry granules; the obtained dry granules are soft; Granulation: The dry granules are passed through a 24-mesh sieve through an oscillating granulator to obtain granules; Total mixing: mixing silicon dioxide and whole granules evenly, then adding antioxidant and magnesium stearate and mixing evenly to obtain total mixed granules; Tableting: The total mixed granules are tableted, and the loading amount is adjusted during tableting so that the tablet weight is 0.6-0.8 g, and the tablet press pressure is adjusted so that the tablet has the maximum hardness during compression, thereby obtaining a high-content broken-wall Ganoderma lucidum spore powder tablet.
[0068] Test Example 1 Multiple quality inspections were conducted on the plain tablets or coated tablets of Example 1, Example 2, Example 5, Example 6 and Comparative Example 1, Comparative Example 2, and Comparative Example 3.
[0069] 1. The appearance (including discoloration and staining) of the plain tablets and coated tablets (i.e., the final products) obtained in each embodiment and comparative example was recorded. Ten tablets were randomly selected from the plain tablets and the final products of each embodiment and comparative example to examine their taste. The results are shown in Table 1.
[0070] Table 1 Appearance and taste
[0071] 2. According to the general rules of the four volumes of the 2020 edition of the Chinese Pharmacopoeia, the tablet weight difference, hardness, friability and disintegration time of the final products obtained in each embodiment and comparative example were investigated: 20 tablets were randomly selected from the plain tablets of each example to examine the tablet weight differences. The tablet weight differences of the final products of each example are shown in Table 2.
[0072] Table 2 Tablet weight differences
[0073] Five groups of samples were randomly selected from the plain tablets of each embodiment and comparative example, with 6 tablets in each group, and their hardness was examined. The hardness of each group of final products of each embodiment is shown in Table 3.
[0074] Table 3 Hardness
[0075] Five groups of samples were randomly selected from the plain tablets of each embodiment and comparative example, with 10 tablets in each group, and their friability was examined. The friability of each group of final products of each embodiment is shown in Table 4.
[0076] Table 4 Friability
[0077] Five groups of samples were randomly selected from the plain tablets of each embodiment and comparative example, with 6 tablets in each group, and their disintegration time was investigated. The disintegration time of each group of the final product of each embodiment is shown in Table 5.
[0078] Table 5 Disintegration time
[0079] 3. Stability inspection Five groups of samples were randomly selected from the final products of each embodiment, with 10 tablets in each group, and the disintegration time and peroxide value of each group of samples were examined.
[0080] 100 tablets were randomly selected from the final products of Examples 1, 2 and Comparative Example 2 and placed in a high temperature box at 45°C and away from light for 7 days. Five groups of samples were randomly selected from the samples after being placed for 7 days, each group having 16 tablets, of which 10 tablets were used to examine their peroxide value after being placed at high temperature, and 6 tablets were used to examine their disintegration time after being placed at high temperature.
[0081] The disintegration time of each group of final products before and after high temperature placement is shown in Table 6 and Table 7, and the peroxide value of each group of final products before and after high temperature placement is shown in Table 8 and Table 9.
[0082] Table 6 Disintegration time before high temperature storage
[0083] Table 7 Disintegration time after high temperature storage
[0084] Table 8 Peroxide value before high temperature storage
[0085] Table 9 Peroxide value after high temperature storage
[0086] 100 tablets were randomly selected from the final products of Example 1 and Example 2 and placed at 37°C, 75% RH, and away from light for 3 months. Three groups of samples were randomly selected at 0, 1, 2, and 3 months, with 6 tablets in each group, to examine their disintegration time after high temperature and high humidity placement. The results are shown in Table 10.
[0087] Table 10 Disintegration time before and after high temperature and high humidity storage
[0088] It can be seen from the above experimental results that the plain tablets obtained in Example 1 and Example 2 have good appearance, but are easy to stain other contact objects; the appearance and taste after coating are good; the tablet weight difference is less than 5%, which meets the basic requirements of tablets; the hardness of the plain tablets is greater than 90N, and the weight loss of brittleness accounts for 0%, which is suitable for coating, and the effect after coating is good; the disintegration time does not exceed 9Min, which is easier to disintegrate and meets the requirements; the high temperature investigation results show that the peroxide value of the final products obtained in Example 1 and Example 2 has no significant change before and after high temperature placement, and the disintegration time has no significant change; the accelerated investigation results show that the disintegration time of the final products obtained in Example 1 and Example 2 has no significant change after being placed under high temperature and high humidity conditions for 3 months. The above results prove that the high-content broken wall Ganoderma lucidum spore powder tablets in Example 1 and Example 2 meet the basic requirements of tablets and can meet market requirements.
[0089] The samples of Example 5 are good in appearance and taste; the difference in tablet weight is small, meeting the basic requirements of tablets; the hardness of this batch is greater than 90N, the weight loss of friability accounts for 0%, suitable for coating, and the effect after coating is good; the average disintegration time is 8Min, which is easy to disintegrate. The results of the high temperature investigation experiment show that the peroxide value of the sample of Example 5 changes greatly without adding antioxidants, and the sample is easily oxidized.
[0090] The sample of Example 6 has good appearance and taste, but due to the color of the Ganoderma lucidum spore powder itself, it is easy to stain other objects that have been in contact with it; the difference in tablet weight is small, meeting the basic requirements of tablets; the hardness is greater than 90N, and the weight loss of friability accounts for 0%; the disintegration time is an average of 9 minutes, which is easy to disintegrate. The results of the high temperature investigation experiment show that the peroxide value of the sample of Example 6 has not changed significantly, but compared with the high temperature investigation experiment of Example 1, it can be seen that the coating is more conducive to the anti-oxidation of the product.
[0091] In Comparative Example 1, povidone K30 is used instead of hydroxypropyl methylcellulose. The granulation process is more difficult and the granules are harder, which may be the reason why the appearance of the plain tablet sample is uneven; although the tablet weight is within the deviation range, it is at a relatively high tablet weight difference value; the hardness is less than 40N, which is low and not conducive to coating; although the weight loss ratio of friability is less than 1%, it is at a relatively high weight loss ratio; the disintegration time is an average of 9 minutes, which is easier to disintegrate; due to the low hardness and friability, it is not suitable for coating, and there are more fragments after coating and heavier adhesion.
[0092] In Comparative Example 2, corn starch was used instead of sodium carboxymethyl starch, and the sample had a good appearance and taste; the tablet weight difference was small; the average hardness was 84.6N, and the weight loss of friability accounted for 0%, which was suitable for coating, and the effect after coating was good; the disintegration time was long, and it was not easy to disintegrate, which did not meet the requirements of the tablet for the disintegration time limit; the results of the high temperature investigation experiment showed that the disintegration time was significantly increased after high temperature placement.
[0093] Comparative Example 3 adopts a common one-step granulation process to prepare granules, but the dry granules obtained after granulation are soft, which is not conducive to tableting, and the plain tablets have low hardness and high brittleness, which is not conducive to coating.
[0094] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A high-content broken-wall Ganoderma lucidum spore powder tablet, characterized in that: The invention comprises the following raw materials in parts by weight: 50-60 parts of broken wall Ganoderma lucidum spore powder, 30-40 parts of sorbitol, 3-5 parts of hydroxypropyl methylcellulose, 5-6 parts of sodium carboxymethyl starch, 2.5-3.5 parts of silicon dioxide, and 0.8-1.2 parts of magnesium stearate.
2. The high-content broken-wall Ganoderma lucidum spore powder tablet according to claim 1, characterized in that: The invention comprises the following raw materials in parts by weight: 50-60 parts of broken wall ganoderma lucidum spore powder, 30-40 parts of sorbitol, 3-5 parts of hydroxypropyl methylcellulose, 5.5 parts of sodium carboxymethyl starch, 3 parts of silicon dioxide and 1 part of magnesium stearate.
3. The high-content broken-wall Ganoderma lucidum spore powder tablet according to claim 1 or 2, characterized in that: The wall-breaking rate of the wall-broken Ganoderma lucidum spore powder is not less than 98%; and / or The viscosity of the hydroxypropyl methylcellulose is 50 mPa·s; and / or The raw materials of the high-content broken-wall Ganoderma lucidum spore powder tablets also include antioxidants.
4. The high-content broken-wall Ganoderma lucidum spore powder tablet according to claim 3, characterized in that: The antioxidant is one or both of vitamin C and vitamin E; and / or The weight portion of the antioxidant is no more than 0.1 part.
5. The high-content broken-wall Ganoderma lucidum spore powder tablet according to claim 4, characterized in that: The antioxidants are 0.01-0.02 parts of vitamin C and 0.005-0.0085 parts of vitamin E.
6. The method for preparing the high-content broken-wall Ganoderma lucidum spore powder tablet according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1. According to the principle of equal and increasing mixing, the broken wall Ganoderma lucidum spore powder, sorbitol, hydroxypropyl methylcellulose and sodium carboxymethyl starch are uniformly mixed to obtain a mixed powder; S2, adding water to the mixed powder to obtain a soft material, granulating to obtain wet granules; drying the wet granules until the moisture content of the granules is 2.5% to 5.0% to obtain dry granules; granulating the dry granules to obtain granulated granules; S3, uniformly mixing the whole granules with silicon dioxide, antioxidants, and magnesium stearate to obtain total mixed granules; S4, tableting the total mixed granules to obtain the high-content broken-wall Ganoderma lucidum spore powder tablets.
7. The preparation method according to claim 6, characterized in that: The particle size of the broken spore powder of Ganoderma lucidum in S1 is less than 550 µm, the particle size of sorbitol is less than 830 µm; the particle size of hydroxypropyl methylcellulose is less than 180 µm, and the particle size of sodium carboxymethyl starch is less than 180 µm; and / or The mass ratio of the mixed powder to water in S2 is 100:(27-33); and / or The granulation mesh in S2 is 20-24 mesh; and / or The drying temperature in S2 is 40-50° C.; and / or The sieve mesh of the granules in S2 is 24 mesh; and / or In S3, the silicon dioxide is firstly mixed with the whole granules, and then the antioxidant and magnesium stearate are added and mixed evenly; and / or During tableting as described in S4, the tablet weight is adjusted to 0.6-0.8 g, and the pressure is adjusted so that the maximum hardness of the tablet is obtained during compression.
8. The preparation method according to claim 7, characterized in that: The preparation method further comprises coating the high-content broken-wall Ganoderma lucidum spore powder tablets obtained in S4.
9. The preparation method according to claim 8, characterized in that: The coating is a gastric soluble film coating.
10. The preparation method according to claim 9, characterized in that: The coating operation is as follows: dissolving the coating material in 70% to 80% ethanol with a solid-liquid ratio of (8 to 12): (88 to 92) to obtain a coating solution; coating is performed with the coating solution with a coating weight gain of 3.5% to 4.5%.